2017
DOI: 10.1073/pnas.1618201114
|View full text |Cite
|
Sign up to set email alerts
|

Pacific North American circulation pattern links external forcing and North American hydroclimatic change over the past millennium

Abstract: Land and sea surface temperatures, precipitation, and storm tracks in North America and the North Pacific are controlled to a large degree by atmospheric variability associated with the Pacific North American (PNA) pattern. The modern instrumental record indicates a trend toward a positive PNA phase in recent decades, which has led to accelerated warming and snowpack decline in northwestern North America. The brevity of the instrumental record, however, limits our understanding of long-term PNA variability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Together, these regional data suggest that increased winter snow accumulation may have contributed to positive mass balances on glaciers throughout southern coastal Alaska. This conclusion is supported by proxy records in downwind North America, where reconstructions of the wintertime PNA exhibit shifts toward more positive PNA patterns in the early CE 1800s, a teleconnection pattern that also implies a strengthening AL and hence increased winter precipitation in the GOA (Figure 8C; Liu et al, 2017). Additionally, oxygen-isotope proxies of paleoclimate from carbonates in lake sediment and from the Mount Logan ice core suggest that an abrupt shift to a stronger AL occurred between the mid-18th and early-19th centuries ( Figure 8D; Fisher et al, 2004;Anderson et al, FIGURE 8 | Shifts or trends toward a stronger Aleutian Low pressure system preceded the 19th century glacier advance in Coastal Alaska (blue box).…”
Section: Paleo-records Show the Importance Of Winter Precipitation Fosupporting
confidence: 56%
See 1 more Smart Citation
“…Together, these regional data suggest that increased winter snow accumulation may have contributed to positive mass balances on glaciers throughout southern coastal Alaska. This conclusion is supported by proxy records in downwind North America, where reconstructions of the wintertime PNA exhibit shifts toward more positive PNA patterns in the early CE 1800s, a teleconnection pattern that also implies a strengthening AL and hence increased winter precipitation in the GOA (Figure 8C; Liu et al, 2017). Additionally, oxygen-isotope proxies of paleoclimate from carbonates in lake sediment and from the Mount Logan ice core suggest that an abrupt shift to a stronger AL occurred between the mid-18th and early-19th centuries ( Figure 8D; Fisher et al, 2004;Anderson et al, FIGURE 8 | Shifts or trends toward a stronger Aleutian Low pressure system preceded the 19th century glacier advance in Coastal Alaska (blue box).…”
Section: Paleo-records Show the Importance Of Winter Precipitation Fosupporting
confidence: 56%
“…(B) Accumulation rate of snow on Mount Hunter in the Alaska Range (Winski et al, 2017). (C) Reconstructed Pacific North American atmospheric circulation pattern based on tree rings and varved lake sediments from downwind North America, where more positive values coincide with a stronger Aleutian Low (Liu et al, 2017). (D) Oxygen isotopes of carbonate deposited in Jellybean Lake in the Yukon Territory (Anderson et al, 2005).…”
Section: Paleo-records Show the Importance Of Winter Precipitation Fomentioning
confidence: 99%
“…PNA is known to exert strong control over winter storm tracks across North America (Wallace and Gutzler ). Previous work has suggested a weak association between PNA and 20th‐century winter precipitation anomalies (Leathers et al ) in the southwestern USA, although long‐term paleoclimate data have suggested that variation in PNA is correlated with drought in the region over the past millennium (Liu et al ). This correlation suggests that long‐term trends in the PNA pattern, such as those suggested by paleoclimate records (Liu et al ), could impact future winter precipitation and water resources in the Navajo Nation.…”
Section: Discussionmentioning
confidence: 98%
“…Several modeling studies have investigated how greenhouse warming affects changes in the PNA mean state and found a trend toward a more PNA+ pattern in response to increased greenhouse gas emissions (Allan et al, 2014;Chen et al, 2018;Gan et al, 2017;Ning & Bradley, 2016;Zhou et al, 2014). There is also some geological evidence that the twentieth century PNA patterns tend to be more positive than those of the past centuries or millennia (Hubeny et al, 2011;Liu et al, 2017;Moore et al, 2002;Trouet & Taylor, 2010). However, few studies have explored how extreme PNA events will change in response to greenhouse warming.…”
Section: Introductionmentioning
confidence: 99%